Malignant Brenner tumor of the ovary: Pathologic evaluation, molecular insights and clinical management - Tiannan Wang; Wei Huang; Brian S Finkelman; Huina Zhang (Elsevier, 2024)
Malignant Brenner tumor (MBT) of the ovary is exceedingly rare, and studies of MBT have been limited to case reports and small case series. MBT shares similar clinical and radiological presentations with other ovarian epithelial malignancies, and the diagnosis of MBT is predominantly based on histopathologic evaluation. Recently, relatively large retrospective studies have advanced understanding of their histogenesis and malignant transformation, as well as on the clinical management of this rare subtype of ovarian carcinoma. In this article, we review the published English literature on MBT, with an emphasis on the histopathologic evaluation, molecular biology, and clinical management of MBT.